Implementasi K-pop Star Pada Perancangan Interior Korean Wave Exhibition Center di Surabaya - S.P Honggowidjaja, Rebecca Chandra (Intra, 2013)
Korean wave is a music phenomenon become popular in Korea and throughout the world, including in Indonesia itself. Many of the people of Indonesia who have "fever" K-pop, they are made up of mostly young women. In Surabaya alone, many in dirikannya fanclub for their respective idols, like ELF surabaya, surabaya Sone, Beauty, and so on. Not only in terms of music, but drama tv, culture, style clothing, food, traditional clothing until they had always wanted to know and learn. But the problem is they do not have a place to gather and facilitate their activities, because that is in need of a facility that can inform openly information they want to know, collections, history, and other facilities that they need about korean wave